Verifiable Top-k Query Processing in Tiered Mobile Sensor Networks. (18th October 2015) - Liu, Fangju; Ma, Xingpo; Liang, Junbin; Lin, Mugang
Verifiable top- k query processing in tiered sensor networks, which refers to verifying the authenticity and the completeness of top- k query results received by the network owner in tiered sensor networks, has received attention in very recent years. However, the existing solutions of this problem are only fit for static sensor network. In this paper, we try to solve the problem in a tiered mobile sensor network model, where not only static sensor nodes but also mobile sensor nodes existed. Based on the tiered mobile sensor network model, we propose a novel verifiable scheme named VTMSN for fine-grained top- k queries. The main idea of VTMSN is as follows: it maps each of the positions where sensor nodes are in a static state to a virtual node and then establishes relationships among data items of each virtual node with their score orders, which are encrypted along with the scores of the data items and the time epochs using the distinct symmetric keys kept by each sensor node and the network owner. Both theory analysis and simulation results show the efficiency and the security of VTMSN.